The Document Delivered to Lord Balfour on the Eve of the British Cabinet’s Decision on the Declaration of Support for a National Homeland (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2025)
On the eve of the final and decisive discussion of the British War Cabinet to issue a declaration of support for the establishment of a national homeland for the Jewish people in Palestine, Sir Mark Sykes, a British diplomat serving as Secretary ofthe Cabinet, delivered a memorandum to Foreign Secretary Lord Arthur Balfour describing the high agricultural potential of Palestine’s various regions. In the summary of the memorandum, it was estimated that with a modest investment and prudent agricultural cultivation, it would be possible to double the country’s population within seven years without displacing any of its existing inhabitants.The summary was written and submitted to Balfour as a response to a detailed memorandum prepared a few days earlier by Lord George Curzon, one of the cabinet members. Curzon expressed reservations about issuing the requested declaration ofsupport, primarily arguing that the land was not very arable and incapable, in his view, of sustaining the Jewish people were they to immigrate there. During the cabinet discussion, Balfour sought his colleagues’ support for apro-Zionist declaration. He addressed Curzon’s reservations, relying in part on the document he had received from Sykes. After a brief discussion, the cabinet approved the decision to issue the declaration.The article offers a close reading of the summary delivered by Sykes to Balfour, showing that it was very likely written by agronomist Aaron Aaronsohn - discoverer of wild wheat and founder of the NILI underground. Aaronsohn arrived in London in the autumn of 1917, and Sykes invited him to participate in the discussions between Zionist leaders Chaim Weizmann and Nahum Sokolow and senior officials in the British Foreign Office regarding the pro-Zionist declaration. The memorandum in question was another link in the cooperation between him and Sykes as part of forging the alliance between the Zionists and the British during World War I.
Keywords: Aaron Aaronsohn; Arthur Balfour; Balfour Declaration; Mark Sykes; Palestine